Design Evaluation Of Hydraulic Pumping Unit At Well Alf-04 Kawengan Field - Indarti, Adrian; Nasution, Alfisyahri (Gema Wiralodra, 2024)
The methods of lifting fluid from the well to the surface consists of natural wells method and artificial lift method. One type of artificial lifting is Hydraulic Pumping Unit (HPU) method. In this case, well ALF-04 as the HPU well in Kawengan field which faces lower actual production compare to its theoritic production calculation then decided need to be redesigned. The objectives of redesigned is to reach optimum flow rate of the well. Recently actual flow rate of this well is 309.2 bfpd, and then the result of IPR calculation by Vogel shows the Q max is 957.25 bfpd, it means this well production is still feasible to be optimized till approximately 765.8 bfpd. After redesign calculation , obtained pump setting  depth 755 m, plunger size of 2.5 ", 120" stroke length, and speed of 6 spm, pump displacement 568.425 bpd. For the rod diameter was changing from 0.75 inch to 0.875 inch with total length 2395m , it greatly affects the maximum stress value of 22,774.03 psi, and also has an influence to the increasing of PPRL value of 8243.26 lb, and the MPRL value of 3000 lb.